Dyslexia: A Visual Disorder? - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Visual evoked potentials were measured with scalp electrodes in eight reading-disabled children aged 8 to 11 years and compared to a control group of 13 age-matched normal readers at the School of Optometry, University of Missouri, St Louis.